Evaluation of Health-Related Quality of Life Post-Liver Transplantation in Paediatrics - Naureen, Sobia; Nasir, Hanana; Adhami, Saad; Seerat, Iqtadar (Indus Journal of Bioscience Research, 2025)
Objective: For liver failure patients, liver transplantation is the only effective therapy option. With higher postoperative survival rates, more focus is required on patient quality of life as a marker of successful liver transplantation. This research evaluates the quality of life following surgery in juvenile liver transplant patients. Methodology: This study was designed as a prospective cross-sectional survey to assess the quality of life of patients. It was conducted at the Pakistan Kidney and Liver Institute and Research Centre (PKLI&RC) over a period spanning from July 2021 to February 2023. Liver transplant recipients, under 15 years, visited OPD at least 6 months after surgery were considered in the study. Quality of life was measured using WHOQOL-BREF. As per scoring guide the scores were converted to 100 sclae. Results: In this study, 41 liver recipients participated in the study. Out of 30 alive, most of the 24(80%) liver transplant recipients were aged between 1 to 10 years. Among them 22(73.3%) were male. Overall mean quality of life and general health was 92.33±11.65 (range 60 to 100), mean physical health score was 79.05±5.22 (range 68.57 to 88.57), mean psychological health was 86.22±5.08(range 76.67 to 96.67), Social relationships was 97.33±6.91 (range 70 to 100) and environment was 88.33±5.51 (range 80 to 100). Conclusions: Liver transplantation leads to an improvement in quality of life as compared to the pre-transplant state. This study will aid in better defining expectations for patients and their families, as well as directing the clinical course following liver transplantation. Transplant teams may also target early interventions.